Situations referring to the organization, classification and management of economic data - ŞERBAN, Măriuţa; HURLOIU, Lăcrămioara-Rodica; ŞTEFAN, Raluca-Mariana; HURLOIU, Iulian-Ioan (Annals of Spiru Haret University. Economic Series, 2015)
An efficient information system provides relevant, accurate, reliable and timely information to users. This information is stored as data in files, which must be arranged and maintained so that users can easily obtain the information they need. Data management is a very important part of the economic organizational information system because it influences the speed with which data can be obtained and, therefore, the decision may be taken. There are times when speed decision is vital to the economic organization. Such information systems, resource data type must be organized and structured in a logical way that allows easy access, efficient processing, fast data access and effective management.